Site-based mapping for parallel proxy servers with fewer TCP connections. - Kin-Yeung Wong (IEEE Network : the magazine of global information exchange)
Many mapping schemes for parallel proxy servers have been proposed in previous research. The operations of these schemes are mainly URL-based, and therefore cannot fully benefit from the new persistent connection feature of HTTP/1.1. In this article we propose a site-based mapping scheme that forwards all requests targeting the same Web site to the same proxy server. This allows a proxy to leave the TCP connections open between consecutive operations so as to avoid the costs of multiple open and close connections to the remote servers. Simulation results show that the proposed site-based scheme reduces 40-70 percent of connection setups and teardowns compared to conventional URL-based mapping schemes.